Memoricídio, genocídio e resistência: a trajetória de M.I.A e o Y da encruzilhada - Escobar, Nuncia Gabriele Guimarães (2022)
In the research presented here, we seek to understand and explain, through the Case Study and Trajectory Analysis methodologies, the way in which Memoricide, Genocide and Resistance are articulated and related to Coloniality. The case studied starts from interventions in cultural heritage, but spreads beyond the spheres of culture, that is, it reflects the economic determinations, since the historical-structural processes of colonialism left imperialist legacies in the social imaginaries, but they are also responsible for the dynamics of overexploitation, underdevelopment and inequality. We rely on a theoretical framework derived from Cultural Studies, World-System Analysis and the Marxist Dependency Theory to contextualize global coloniality and delve into specific cases of local coloniality that exemplify the way in which the annihilation of non-white memories and knowledge intrinsically corroborates the imminent murder of indigenous and black bodies. Therefore, we made the effort to seek the elements that explain the dialectical and inseparable relationship between Memoricide - from the disputes in the symbolic scope, mainly with regard to Colonial Cultural Heritage - and Genocide – from the concreteness of the facts about who dies and who kills, a debate raised worldwide with the Black Lives Matter movement – as they are governed by the colonial/necrocapitalist world-system. In this perspective, the theoretical path deconstructs the fictitious and binary dilemmas between Symbolic and Material, between Culture and Economy, to conclude, in the empirical field, that nothing is strictly cultural or strictly economic, coloniality is at the crossroads. The impacts of the Resistance, especially in the context of the fight against racism, in the city of São Paulo, show this. Our main interlocutor is the artist, pixador and militant M.I.A who, both in collective actions in the movements and in his personal trajectory, contemplates the scopes of Memoricide (monuments, museums and street art) and Necropolitics (hunger, police brutality, genocide).